Komparasi Pengelolaan Sampah TPST Kartoharjo dan TPS 3R Payaman Terhadap Pengurangan Timbulan Sampah Kecamatan Nganjuk: Comparison of Waste Management between TPST Kartoharjo and TPS 3R Payaman in Reducing Waste Generation in Nganjuk District - Ingtyas, Awang Pambagya Manggar; Mirwan, Mohammad (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The rapid economic growth correlated with population growth has resulted in increased activities and consumption by society, which in turn increases waste production. If waste continues to accumulate, it will certainly pollute the surrounding environment. In waste management in Nganjuk Regency, especially in the Nganjuk District area, there are TPST Kartoharjo and TPS 3R Payaman which manage waste with different systems. Waste generation in Nganjuk District is 2,577.73 tons per year. TPST Kartoharjo can process waste up to 97.20% while TPS 3R Payaman is 70.32%.